ANALYSIS OF IMPACT OF SELECTED GROUP OF FACTORS OF VEHICLE WORK CONDITIONS ON THE FUEL CONSUMPTION - Holesa, Lukas; Sarkan, Branislav (Doprava a spoje, 2012)
Strived in the contribution to reflect the area of fuel consumption of motor vehicles. It is the consumption that is currently a key issue of carriers as well as individual motorists. The contribution contains determination of the most important factors stemming from work conditions of the vehicle, i.e. predominantly related to traffic (road) conditions (representing external factors affecting the vehicle). The attention is furthermore paid to the analysis and description of the impact of selected factors, implied by characteristics of the traffic flow, on the fuel consumption.